A Simple Technical Tip for Removal of Intramedullary Broken Drill Bit. Issue 4 (December 2019) - Balaji, Gopisankar; Menon, Jagdish; Sharma, Deep
Abstract : A 35-year-old man presented to us with nonunion of both bones of the right forearm. He was planned for open reduction and internal fixation. Intraoperatively while trying to open the medullary canal of the ulna with a 2.5-mm noncannulated drill bit, the distal end of the drill bit broke and was stuck within the medullary cavity. Under image intensifier, the broken piece was retrieved with the help of a long depth gauge from the 4.5-mm system. This technique is simple, cost-effective, and less time-consuming.